LINGUISTOCULTURAL FEATURES OF WORDS MEANING PLACE NAMES IN UZBEKISTAN AND ENGLISH: A REFLECTION OF NATIONAL IDENTITY AND CULTURAL MEMORY - Yoldoshboyeva Zulhumor Mashrabjon kizi,Parviz Izzatillayev (International Journal of Literature and Language Studies, 2026)
This article provides a comparative-typological analysis of the linguocultural features of words denoting place names (toponyms) in the Uzbek and English languages. The main aim of the study is to reveal the national identity, cultural memory and worldview reflected in toponymic units. Toponyms are regarded not merely as labels designating geographical objects, but as cultural codes preserving the historical experience, beliefs, values and collective consciousness of a people. The findings demonstrate that concepts such as nature, fertility and spiritual-religious notions prevail in Uzbek toponymy, whereas concepts of land ownership, social structure and industrial heritage dominate English toponymy.